Effect of Dragon Fruit Extract (Hylocereus polyrhizus) in Drinking Water on The Quality of Isa Brown Chicken Eggage 25-30 Weeks. - N. M. Y., Andriyani; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to determine the effect of dragon fruit extract ( Hylocereus polyhizius ) in drinking water on the quality of Isa Brown chicken eggs aged 25-30 weeks. This study was conducted at the Kandang Faculty of Animal Husbandry, Bukit Jimbaran Campus, which lasted for 5 weeks. The egg quality test was carried out at the Poultry Laboratory, Faculty of Animal Husbandry, Sudirman Campus, Denpasar. The research design used was Completely Randomized Design consisting of 2 treatments of Isa Brown chicken given 0% dragon fruit extract in drinking water (R0) and chicken Isa Brown was given 5% dragon fruit extract in drinking water (R1), each treatment was repeated 9 times each replication consisted of 3 laying hens of Isa Brown so that the total chicken used was 54. The variables observed were external quality including egg weight and egg index, and internal quality including eggshell thickness, eggshell weight, pH, yolk color, haugh unit (HU). The results showed that egg weight, eggshell thickness, eggshell weight, egg yolk color and haugh unit (HU) R1 treatment were real (P <0.05) better than R0 treatment. Whereas the egg index and egg pH on the R0 treatment were not real (P> 0.05) compared to R1. Based on the results of the study it can be concluded that the Chicken Isa Brown with the administration of 5% dragon fruit extract in drinking water with commercial rations gave better quality to egg weight, eggshell thickness, eggshell weight, egg yolk color and haugh unit (HU) and no effect the index of egg shape and pH of eggs. Keywords : Isa Brown, quality of eggs, dragon fruit extract